2016
DOI: 10.11114/ijsss.v4i12.1986
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Coresidence: Difficulties and Benefits of Israeli Arab Emerging Adults Who Live with Their Parents

Abstract: This qualitative study focuses on Israeli Arab emerg ing adults who live at home with their parents, and explores their experience as to the benefits and difficulties of prolonged coresidence. Semi-structured open interviews were conducted with 16 Arab emerg ing adults (8 women, 8 men), who live at home with their parents. Findings reveal that most participants live with their parents out of respect to cultural norms. While doing so they experience amb ivalence: The benefits are family support and convenient l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…It is possible that by living at home, and hence by fulfilling the parents' expectation not to leave before marriage, the Arab parents experience obedience from their children, which is an important value in the Arab family. A recent study (Dor & Hallifa-Yunnis, 2016), focused on the experience of Israeli Arab emerging adults who live with their parents. The findings revealed that the need to conform to the social expectation that children live in their parents' home until marriage, gives these emerging adults a degree of comfort, as their parents are satisfied that they fulfill society's norms.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that by living at home, and hence by fulfilling the parents' expectation not to leave before marriage, the Arab parents experience obedience from their children, which is an important value in the Arab family. A recent study (Dor & Hallifa-Yunnis, 2016), focused on the experience of Israeli Arab emerging adults who live with their parents. The findings revealed that the need to conform to the social expectation that children live in their parents' home until marriage, gives these emerging adults a degree of comfort, as their parents are satisfied that they fulfill society's norms.…”
Section: Discussionmentioning
confidence: 99%